Uromodulin (Tamm–Horsfall protein): guardian of urinary and systemic homeostasis. Issue 1 (14th January 2019) - Micanovic, Radmila; LaFavers, Kaice; Garimella, Pranav S; Wu, Xue-Ru; El-Achkar, Tarek M
Abstract: Biology has taught us that a protein as abundantly made and conserved among species as Tamm–Horsfall protein (THP or uromodulin) cannot just be a waste product serving no particular purpose. However, for many researchers, THP is merely a nuisance during urine proteome profiling or exosome purification and for clinicians an enigmatic entity without clear disease implications. Thanks to recent human genetic and correlative studies and animal modeling, we now have a renewed appreciation of this highly prevalent protein in not only guarding urinary homeostasis, but also serving as a critical mediator in systemic inter-organ signaling. Beyond a mere barrier that lines the tubules, or a surrogate for nephron mass, mounting evidence suggests that THP is a multifunctional protein critical for modulating renal ion channel activity, salt/water balance, renal and systemic inflammatory response, intertubular communication, mineral crystallization and bacterial adhesion. Indeed, mutations in THP cause a group of inherited kidney diseases, and altered THP expression is associated with increased risks of urinary tract infection, kidney stone, hypertension, hyperuricemia and acute and chronic kidney diseases. Despite the recent surge of information surrounding THP's physiological functions and disease involvement, our knowledge remains incomplete regarding how THP is normally regulated by external and intrinsic factors, how precisely THP deficiency leads to urinary and systemic pathophysiology and in what clinical settings THP can be used as a theranostic biomarker and a target for modulation to improve patient outcomes.